Remediation of Chromium Contaminated Soil by Phyto-Bio System (PBS) Application - Retno Rosariastuti; Selly Maisyarah; Sudadi Sudadi; Sri Hartati; Purwanto Purwanto (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2019)
Chromium polluted water was increased as the result of the growth of the industries, due to their industrial waste were most likely contain heavy metals, especially textile industrial waste that was discarded to the rivers. This research aimed to study the removal of chromium levels in soil used the symbiosis between plant and bacteria. Soil sample contained with 4.33 mg kg-1 and the irrigation water sample contained with 1.09 mg l-1 of total chromium. This research design was factorial with Randomized Complete Block Design as the based design There were 3 factors in this study: 1.  inorganic fertilizer (P): P0: without inorganic fertilizer, P1: with inorganic fertilizer; 2. chelator (B):B0: without chelator, B1: with chelator Rhizobium sp I3, B2: with chelator manure; 3. Plant (T): T0 without plant, T1: with plant. Data were analyzed by statistical analysis using ANOVA continued by T-test or Duncan Multiple Range test and correlation test. The result showed that the remediation process reduced chromium levels in soil with the removal effectivity up to 71.90% on the treatment combination of NPK fertilizer+manure+plant while removal effectivity on plant-only treatment was 55.66%. The chromium levels in Fimbristylis globulosa were in the range from 1.82–3.15 μ g-1, it indicated that Fimbristylis globulosa was a feasible plant for bioremediation. Fimbristylis globulosa grew well and has the ability to absorb chromium, especially by combining it with Rhizobium sp I3and the chromium uptake in roots was higher than shoots.